Clinical analysis of post sterilization failure cases in a tertiary hospital - Rathod, Setu; Samal, Sunil Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The most common permanent method of family planning accepted in India is female tubal sterilization as it has a very low failure rate of 0.1-0.8% in the first year and overall pregnancy chances of 1 in 200. It can be done by open method but laparoscopic method has now gained wide popularity. Methods: Ours was a retrospective study of post sterilization failure cases admitted to Department of Obstetrics and Gynecology, Mahatma Gandhi medical College and Research Institute, Pondicherry within a 3 year time period between May 2014 to May 2017. Results: Within a 3 year period, 3 patients presented with intrauterine pregnancy whereas 28 presented as ectopic pregnancy following sterilization. Majority of patients belonged to 26-30 year age group and had 2 children. 35.7% of ectopics presented at 7-8 weeks gestational age. Over 70% of sterilization failures were done by open method and around 43% were done during caesarean section. Around 71.4% sterilization failures were seen within 5 years of sterilization but 1 patient presented as late as 17 years post sterilization. Conclusions: Female sterilization may result in failure even after years of sterilization. In present study, open sterilization had a higher failure rate than laparoscopic sterilization. The most common mode of sterilization failure was ectopic pregnancy. Therefore, patients undergoing sterilization must be counseled about chances of failure; even though it is a permanent method, and to consult immediately if missed period else at a later stage they may go in for rupture ectopic leading to high maternal morbidity and mortality.